2016
DOI: 10.1111/rego.12127
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring multi‐level regulatory governance: Organizational proliferation, coordination, and concentration of influence

Abstract: As regulation increasingly results from the interplay of a wide array of different actors operating at different levels, it has become crucial to focus on how these constellations of regulatory actors operate. Although this research field presents huge potential for theoretical development, we still lack the measurement techniques to allow systematic comparative research. We contribute to filling this gap with four indices measuring crucial characteristics of multi‐actor regulatory arrangements: (i) the scope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 51 publications
1
48
0
2
Order By: Relevance
“…It is true that formal dispositions can, in some cases, lack real effect. However, we argue that this will be less the case regarding the formal delegation of regulatory decision making because regulatory actors have at least two powerful incentives to comply with what is formally stated (Mathieu et al, ). First, following rules and procedures determines the regulators' procedural reputation, which is important for public organizations (Carpenter & Krause, ).…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…It is true that formal dispositions can, in some cases, lack real effect. However, we argue that this will be less the case regarding the formal delegation of regulatory decision making because regulatory actors have at least two powerful incentives to comply with what is formally stated (Mathieu et al, ). First, following rules and procedures determines the regulators' procedural reputation, which is important for public organizations (Carpenter & Krause, ).…”
Section: Methodsmentioning
confidence: 94%
“…Such an approach is not uncommon in the field of regulatory governance (Hanretty & Koop, ; Koop & Lodge, ; Mathieu, Verhoest, & Matthys, ). Previous studies investigated several elements: the institutional characteristics of regulatory agencies and the extent to which they assured independence and accountability; the mechanism provided in legislation to assure coordination in regulatory decision making; and the role of different regulatory actors in regulatory decision making, as indicated in the legislation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, studying these relations between actors by analysing the formal decision-making processes as stipulated in legislation, collaboration agreements and procedures (see, e.g. Koop and Lodge 2014;Mathieu et al 2016) runs the risk of excluding influential actors without a formal decision-making role.…”
Section: Introductionmentioning
confidence: 99%
“…Second, recent research (Aubin and Verhoest, ; Dabbah, ; Ingold et al, ; Koop and Lodge, ; Mathieu, Verhoest, and Matthys, ) has shown that sector regulators must interact with other actors when taking regulatory decisions. Besides the regulator, other public bodies can produce regulation, so it is important to study how the decisions are made and how the interactions occur.…”
Section: Introductionmentioning
confidence: 99%